Introduzione. Popular music e storia: media consumi e politica dagli anni Cinquanta agli anni Novanta - Alessia MASINI (Diacronie. Studi di Storia Contemporanea)
Music is an integral part of human activity, it is an innate “cultural need” and it is an ally of our capacity for abstraction and to perceive the world. It has even been essential to the evolution of the species because it lies at the root of the nature of our language, our anthropological purpose and the formation of societies.